Predictors of Malignancy in Patients With Thyroid Nodule(s) - Alatiar, Islam; Elfol, Hassam; Rageh, Tarek (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2017)
Purpose: To detect the predictors of malignancy in patients with thyroid nodule(s). Background: Thyroid nodules are common surgical problem with 5-10% risk of malignancy. Thyroid surgery is a major operation with many complications. So, it is important to search for the predictors of malignancy in thyroid nodules to spare more benign lesions from surgery. Patients and methods: This prospective study includes 150 patients with thyroid nodule(s), all were admitted for thyroidectomy at Menoufia University Hospital. Demographic and clinical data, ultrasound, fine needle aspiration reports and final histopathology were recorded and analyzed. Patients with previous thyroid surgery or previous neck biopsy were excluded. Results: About 20% of the studied population proved to have malignant nodules on final histopathology reports. Out of 150 cases, there were 83 with multi-nodular goiter and 67 with solitary thyroid nodules. There were higher incidence of malignancy in male patients. The incidence also was higher in solitary nodules than in multinodular goiter. There were statistically significant ultrasound features differences such as; micro-calcifications, ill-defined edges, solid consistency, hypo-echoic pattern, intra-nodular vascularity and size below 2cm. Regarding fine needle biopsy, there were a significant increase in incidence of malignancy from Bethesda(II) – Bethesda(VI) with highest incidence in Bethesda(VI). Conclusion: Predictors of malignancy detected were; male gender, solitary nodules, micro-calcifications, hypo-echoic pattern, ill-defined edges, intra-nodular vascularity, solid nodules, size below 2 cm and Bethesda VI. Large scale multi center studies are needed for more solid statistical result.